DASH Diet Quality and Status of Mental Emotional Disorder among Hypertensive Women in Rural Area - Islami, Diajeng Rochma; Tanziha, Ikeu; Martianto, Drajat; Rachman, Purnawati Hustina (Jurnal Gizi dan Pangan, 2019)
The purpose of this study was to analyse the relationship between diet quality and mental emotional disorder status with the incidence of hypertension in women in rural areas. The study was a cross sectional study with 143 women (71 with normotensive and and 72 with hypertension) in Pondok Bungur Village, Purwakarta District, West Java, Indonesia. The independent variables were dietary qualities based on customized DASH-like diet and mental emotional disorder status, while the dependent variable was hypertension status. Dietary quality was obtained by non consecutive 2 days 24 hours recall, while mental emotional disorder was collected through SRQ 20. Chi-Square and Mann-Whitney were used for data analysis. The DASH-like diet quality of both groups were low thus showed no significant correlation between the DASH diet quality and HT in the study population (p>0.05), as did the status of mental emotional disorder (p>0.05). However, age may be a cofactor in this study because the age differed significantly between the normal and hypertension group (p<0.05). This study shows that there was no difference in dietary quality between HT and non HT group as well as there were no significant correlation between diet quality and mental emotional disorder with HT status albeit segregation by the age group.